2021
DOI: 10.3390/polym13183037
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Aging Properties of Composite Modified Bitumen by Styrene–Butadiene–Styrene and Desulfurized Crumb Rubber

Abstract: Taking advantage of crumb rubber from waste tires to modify bitumen is widely for the environmentally friendly and sustainable development of pavement. This study investigated the modification mechanism, rheological, and aging properties of styrene–butadiene–styrene (SBS)/desulfurized crumb rubber (DCR) composite modified bitumen (SBS/DCRMB). Morphological features and chemical characteristics were assessed by fluorescence intensity measurement and gel permeation chromatography (GPC), respectively, and results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…From the 1930s, the utilize of rubbers from waste rubbers as an additive in the asphalt mixture [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Because of the ability of crumb rubber powder (P) to enhance the asphalt binder and mixture performance [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], therefore, using of crumb rubbers recently increased widely in construction pavement as a probable solution in minimizing waste tires and the disposal areas. Many researchers used composite-modified asphalt containing P and different modifiers, and they examined the characteristics of the composite-modified asphalt through number of micro-analysis methods and property tests [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the 1930s, the utilize of rubbers from waste rubbers as an additive in the asphalt mixture [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Because of the ability of crumb rubber powder (P) to enhance the asphalt binder and mixture performance [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], therefore, using of crumb rubbers recently increased widely in construction pavement as a probable solution in minimizing waste tires and the disposal areas. Many researchers used composite-modified asphalt containing P and different modifiers, and they examined the characteristics of the composite-modified asphalt through number of micro-analysis methods and property tests [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It requires a comprehensive demonstration to determine whether a particular substance is feasible for bitumen modification. By far, many studies have confirmed the success of various kinds of modifiers in the bitumen [ 3 , 4 , 5 , 6 ]. Currently reported modifiers with promising applications are polymers, chemical modifiers, recycled solid waste, and other additives (for instance, adhesion improvers and anti-oxidants) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al adopted the mechanochemical method to prepare desulfurized crumb rubber-modified asphalt and analyzed the effects of desulfurization process variables [ 3 ]. Furthermore, Xu et al investigated the modification mechanism, rheological, and aging properties of SBS/desulfurized crumb rubber composite-modified bitumen [ 4 ]. Zhao et al explored the influence of composite modification of activated crumb rubber powder and SBS on asphalt [ 5 ].…”
mentioning
confidence: 99%